Constitutive and Inducible Aerobic and Anaerobic Stress Proteins in the Echinochloa Complex and Rice. - Mujer, C. V. (1993)
Anaerobic stress resulted in a change in the protein accumulation patterns in shoots of several Echinochloa (barnyard grass) species and Oryza sativa (L.) (rice) as resolved by two-dimensional gel electrophoresis. Of the six Echinochloa species investigated, E. phyllopogon (Stev.) Koss, E. muricata (Beauv.) Fern, E. oryzoides (Ard.) Fritsch Clayton, and E. crus-galli (L.) Beauv. are tolerant of anaerobiosis and germinate in the absence of oxygen, as does rice. In contrast, E. crus-pavonis (H.B.K.) Schult and E. colonum (L.) Link are intolerant and do not germinate without oxygen. Computer analysis of the protein patterns from the four tolerant species and rice indicated that the anaerobic response is of five classes: class 1 proteins, enhanced under anaerobiosis (9 to 13 polypeptides ranging from 16-68 kD); class 2 proteins, unique to anaerobiosis (1 to 5 polypeptides ranging from 17-69 kD); class 3 proteins, remained constant under aerobiosis and anaerobiosis; class 4 proteins, prominent only in air and repressed under anoxia (3 to 7 polypeptides ranging from 19-45 kD); and class 5 proteins, unique to aerobiosis (1 to 4 polypeptides ranging from 18-63 kD). In the intolerant species, E. colonum and E. crus-pavonis, no polypeptides were enhanced or repressed under anoxia (class 1 and class 4, respectively), whereas in the tolerant Echinochloa species and rice, a total of at least 9 to 13 anaerobic stress proteins and 4 to 7 "aerobic" proteins were noted. Immunoblotting identified two of the major anaerobic stress proteins as fructose-1,6-bisphosphate aldolase and pyruvate decarboxylase. Based on the differential response of the intolerant species to anaerobiosis, we suggest that another set of genes, whose products may not necessarily be among the major anaerobic stress polypeptides, might confer tolerance in Echinochloa under prolonged anaerobic stress.